Evaluation and recommendation on Inner Mongolian FDI to Mongolia in the framework of “One Belt, One Road” - Nalin, Naran (Journal of International Studies, 2018)
The Inner Mongolian Autonomous Region plays an important role in the development of bilateral ties between Mongolia and it borders on mountains with Mongolia. The bilateral economic and trade cooperation between Inner Mongolia and Mongolia weigthed position in the framework of China’s “One Belt, One Road” strategy and Mongolia’s “Road Development” initiative. The article aims to assess the situation of Inner Mongolia Autonomous Region and Mongolia, the current investment situation of the two countries, the risks of bilateral cooperation, and the advice of the consultant on ways to improve it.